Recalcitrant granuloma faciale with 14-year follow-up - Keiko Shiba; Reine Moriuchi; Yusuke Morita; Yohei Hamade; Toshinari Miyauchi; Kazuhiro Kikuchi; Kikuo Tsuchiya; Satoko Shimizu (Our Dermatology Online, 2017)
Granuloma faciale (GF) is an uncommon inflammatory dermatosis that is characterized by one or several asymptomatic brown red nodules or plaques usually occurring on the face. GF is known to be extremely resistant to treatment. Various treatments have been attempted, including topical or intralesional or systemic corticosteroids, dapsone, antimalarials, colchicine, topical tacrolimus, and topical psoralen; however, none of these have been found to be reliably efficacious. We tried numerous combinations and rotations of therapeutic modalities for GF over a long time. We described a case of GF in which the eruptions were carefully observed over the course of 14 years before finally resolving. Our experience suggests that continuous and careful follow-up, and trials of combinations and rotations of therapeutic modalities are essential for treating GF.